The reading of the State-Providence actions in the Messages of the Government potiguar in the First Republic (Research, Society and Development, 2018)
In the course of the first republic, the Rio Grande do Norte lived a strong influence of the ideals of the Providence State, where public education was one of the main measures adopted to carry out a new civilizing process, based on positivist ideals of order and progress, as Alfredo Bosi. The documentary corpus studied belongs to the category of official historical sources, so that the Messages of the Government were perceived as a product of the Cultural Elite that ruled the State. To Jean-François Sirinelli, the Cultural Elites are endowed with power, influence and notoriety. In this sense, the objective is to investigate the role of the welfare state in the development of education in the First Republic, based on the discussions of the Cultural Elite present in the annual messages of the potiguar public administration. At first, the teaching offered was harshly criticized. However, it was observed that from 1907 onwards this scenario began to change with the authorization of the Reform of Education and the School Groups were created, which fostered a new progressive resulted in the consolidation of the school culture in Rio Grande do Norte, according to the molds proposed by Dominique Julia. Already in the last year studied, teaching was acclaimed for its efficiency. Finally, it can be concluded that in the speeches of the ruling Cultural Elites, the education situation offered by the State evolved considerably during the First Republic, thanks to the decisive action of the welfare state.